2017
DOI: 10.1111/medu.13475
|View full text |Cite
|
Sign up to set email alerts
|

Using paradox theory to understand responses to tensions between service and training in general surgery

Abstract: Stakeholder responses to the tensions provided temporary relief but were unlikely to lead to real change if the tension between service and training was considered to be an interdependent and persistent paradox. Reframing the service-training paradox in this way may encourage adjusting responses to create effective working partnerships. Our findings add to the body of knowledge on this topic, and will resonate with all those engaged in surgical and other postgraduate training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 74 publications
1
45
0
Order By: Relevance
“…However, our literature search indicated that only infrequently have attempts been made to clarify the precise nature of these different perspectives or tensions (for exceptions see ), or how different factors may interact to cause such tensions in medical education . Instead, typically studies have lacked a theoretical or conceptual underpinning .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our literature search indicated that only infrequently have attempts been made to clarify the precise nature of these different perspectives or tensions (for exceptions see ), or how different factors may interact to cause such tensions in medical education . Instead, typically studies have lacked a theoretical or conceptual underpinning .…”
Section: Methodsmentioning
confidence: 99%
“…This is not about cause and effect but about the figured world of trainees and residents emerging and shifting over time, and what it is that contributes to shifts. For example, where trainee’ and residents’ expectations about how their education needs to be supported are unmet, they may think of quitting training or shifting to another specialty. Are these responses due to the world of medical training not being what they expected, even after many years of observation from the lesser‐powered position of student? Is it because the (often unspoken) expectations they have of their educators are not being meet? What is the co‐construction between individuals, shaped by their history and past experiences (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Cleland et al . use paradox theory to examine a surgical department's responses to the ever‐present tensions between service delivery and training.…”
mentioning
confidence: 99%
“…Cleland et al . suggest that interventions that bring about greater balance still try to compartmentalise training, ‘rather than acknowledging training and service cannot be separated’.…”
mentioning
confidence: 99%